The conjunctival impression cytology between the diagnosed cases of dry eye and normal individuals - Shresta, E; Shrestha, JK; Shayami, G; Chaudhary, M (Nepalese Journal of Ophthalmology, 2011)
Background: The dry eye or tear film dysfunction is a common ophthalmic syndrome. Objective: To compare the results of conjunctival impression cytology between dry eye patients and normal individuals.Subjects and methods: A case control study including consecutive cases of dry eye syndrome was carried out. Individuals without dry eye were taken as control. Impression of conjunctiva with cellulose acetate filter paper was taken from inferonasal bulbar conjunctiva and was stained with Periodic Acid- Schiff (PAS) and counter-stained with haematoxylin and eosin. Main outcome measure: goblet cell density. Results: There was a female preponderance in dry eye disease. Of 114 dry eye cases, 49.2% eyes showed decreased or absent goblet cell density. In 72 normal individuals 73.7% eyes showed normal goblet cell density and 26.3% of eyes showed decreased or absent goblet cells (p < 0.001). The tear break-up time (TBUT) test was significantly more likely to be less than 10 seconds in cases as compared to the controls ( OR = 19.36, 95% CI = 7.56 – 52.52). Similarly, the goblet cell density was likely to be significantly reduced in cases with dry eye syndrome (OR= 2.25, 95% CI = 1.26 – 4.02, p = 0.003). Conclusion: Goblet cell density significantly reduces in dry eye syndrome. The impression cytology is a useful test for the diagnosis of dry eye syndrome. Key words: impression cytology; conjunctiva; dry eyes; tear filmDOI: 10.3126/nepjoph.v3i1.4277Nepal J Ophthalmol 2011;3(5):39-44